2019
DOI: 10.4103/psychiatry.indianjpsychiatry_461_18
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia and depression: How much is the overlap?

Abstract: Background:Previous literature considers insomnia as one of the features, predictor, and also as a residual symptom of depression. However, chronic insomnia and major depressive disorder (MDD) have overlapping features making differentiation between two difficult.Materials and Methods:Forty subjects in each of the three categories-MDD, insomnia (I) and combined diagnoses (MDD-I) were recruited in this study after excluding potential confounders. Diagnosis of MDD was made following Diagnostic and Statistical Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The comorbidity of depression and insomnia disorder did not first attract the attention of researchers, and at first, attention was focused on the latter proposition: that insomnia was a clinical symptom accompanying depressive disorders and that insomnia symptoms would resolve with improvement of depressive symptoms as long as we treated them with antidepressant therapy. Until the early 1990s, several studies showed that preexisting or persistent insomnia symptoms not only failed to resolve with improvement in depressive symptom but instead, increased the risk of depressive episodes and were a risk factor for depressive disorders ( 25 , 26 ). Therefore, one of our aims in this study was to investigate whether the presence or persistence of insomnia symptoms increases the risk of depressive episodes.…”
Section: Discussionmentioning
confidence: 99%
“…The comorbidity of depression and insomnia disorder did not first attract the attention of researchers, and at first, attention was focused on the latter proposition: that insomnia was a clinical symptom accompanying depressive disorders and that insomnia symptoms would resolve with improvement of depressive symptoms as long as we treated them with antidepressant therapy. Until the early 1990s, several studies showed that preexisting or persistent insomnia symptoms not only failed to resolve with improvement in depressive symptom but instead, increased the risk of depressive episodes and were a risk factor for depressive disorders ( 25 , 26 ). Therefore, one of our aims in this study was to investigate whether the presence or persistence of insomnia symptoms increases the risk of depressive episodes.…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 40–43 In addition, psychological factors such as stress and anxiety, which are common to both disorders, may act as a bridge, exacerbating the interdependence between migraine and insomnia. 44–46 The relationship is not only one of comorbidity but also of mutual exacerbation, whereby having one disorder can increase the symptoms and clinical burden of the other. This has significant implications for clinical practice and patient management, as it suggests that treating one condition might have beneficial effects on the other.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 5 ] A number of literatures have also shown that sleep deprivation and depression both have bidirectional relationship. [ 6 7 8 9 ] Depression can have affect on the academic performances of students, hence limiting their career opportunities. [ 10 11 12 13 14 15 ]…”
Section: Introductionmentioning
confidence: 99%